DIGITIZATION OF LIBRARY COLLECTION IN NIGERIAN UNIVERSITY LIBRARIES: UNIVERSITY OF ILORIN LIBRARY EXPERIENCE - SALIU, AJISAFE SALIU (Academy of Social Science Journal, 2017)
The aim of this paper is to discuss the difficulties that the university of Ilorin library encountered in its digitization project and how these difficulties were handled to ensure a robust to digitization outfit. The idea is to alert Nigerian libraries which are yet to embark on digitization on some of the problems or challenges that they are likely to encounter in planning and implementing a digitization project. Admittedly, some of the problems may be unique to university of Ilorin library but it can be said with a fair degree of accuracy that some of Â the problems the university of Ilorin library encountered are general at the planning and the implementation stages. In this paper, the conception, the planning and the implementation stages of the project will be discussed. Problems will be highlighted and suggestions will be made for an effective and efficient digital service delivery.Â